Development of tri-hybrid nanofluids as cutting fluids to enhance performance of end milling process of aluminium alloy 6061-T6 - Wahaizad, Safiei (2022)
Machining of aluminium alloys is extensively complex due to the adherence tendency of aluminium to the tool surface. During machining, the tool wear is mainly affected by forming an adhesive layer and built-up-edge, significantly affecting the machined surface's quality. Several studies are carried out to restrict the heat generated in machining. Among the various alternatives available, the cutting fluids remain to be the choice. Therefore, different techniques are explored to replace the use of cutting fluids. Nowadays, using nanotechnology in science and industry improves the yield of different processes. Hence, machining operations are used as nanofluid and coated cutting tools with nanoparticles. However, their usage in machining is a comparatively primary stage and deserves much attention. The hybrid nanofluids are potential fluids to offer better heat transfer performance and thermophysical properties than single nanofluids. The machining process using hybrid nanofluids requires further research to better understand the mechanism of tool wear and the fundamental aspects are not yet ventured. This study aims to develop tri-hybrid nanofluids as cutting fluids to enhance the performance of the end milling process of AA6061-T6. The tri-hybrid SiO2-Al2O3-ZrO2 nanoparticles were dispersed in 60:40 vol.% of deionized water to ethylene glycol, and concentrations 0.08 and 0.12 wt.% were selected to mix with dispersing agent CTAB at a 1:3 weight ratio. After two weeks of daily visual and UV-Vis spectral examination, the tri-hybrid nanofluids were stable. The zeta potential is higher than 30 mV, suggesting well-dispersed nanoparticles. The uncoated tungsten carbide, single-layered CVD TiCN-Al2O3 and dual-layered PVD TiAlTaN tungsten carbide inserts were used. The study was conducted using cutting speed, feed rate, depth of cut, MQL flow rate and concentration and machining responses of surface roughness, cutting temperature, cutting force, flank wear. Response surface methodology with central composite rotatable design approach is used, and experimental data were validated statistically. SEM micrographs and EDX patterns characterized tool damage. At 0.1 wt.% and 70°C, tri-hybrid nanofluids were 41.1, 10.5 and 20.3 % better thermal conductivity than base fluid, SiO2-Al2O3 and SiO2-ZrO2, respectively. The tri-hybrid nanofluids exhibited 50.5% viscosity enhancement at higher concentrations and lower temperatures. At a higher feed rate, uncoated demonstrated lower surface roughness of AA6061-T6, reflecting the effectiveness of tri-hybrid nanofluids. The cutting temperature below 38 °C improved 84% over the conventional technique. The cutting force was below 30 N, indicating a 35% improvement in process performance. Coated tool exhibited higher cutting force due to coated hardness and various tool failures mechanism. Adhesion, attrition and edge fracture were among of tool failures observed. The absence of BUE is attributed to reduced chip adhesion with higher MQL flow rates and concentrations. Due to coating delamination, coated inserts had worse flank wear than uncoated inserts. However, uncoated tool dominated attrition wear. The optimal end milling parameters were established. The optimum uncoated tungsten carbide cutting conditions were 8440 rpm, 50.1 mm/min feed rate, 0.336 mm cut depth, 1.8 mL/min MQL flow rate, and 0.112 wt% concentration using multi-criteria decision making on parallel coordinates. The application of tri-hybrid nanofluids is the first attempt to enhance single and dual-hybrid thermal-physical properties as well as end milling process performance under high-speed machining. It is strongly recommended to use a newly created tri-hybrid nanofluid with MQL technique in various applications of machining industries.